2018
DOI: 10.1111/wej.12434
|View full text |Cite
|
Sign up to set email alerts
|

A mixing‐length‐scale‐based analytical model for predicting velocity profiles of open‐channel flows with submerged rigid vegetation

Abstract: In open-channel flows with submerged vegetation, the vertical velocity profile can often be described by two layers: the vegetation layer in the lower region and the surface layer in the upper non-vegetated region. In this paper, a new mixing-length scale of eddy is proposed for predicting the vertical velocity profile of flow in an open-channel with submerged rigid vegetation. The analytical model of velocity profile is based on the momentum equation of flow where the turbulent eddy viscosity is assumed to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
(58 reference statements)
1
24
0
Order By: Relevance
“…In the evaluation of the above models and other models, Tang & Ali (2013) and Tang (2019a) showed that the predicted velocity distribution by the above mentioned models is acceptable only for certain experimental datasets, but they do not agree with other datasets. In addition, the predictions by these models show significant differences even for the same dataset.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…In the evaluation of the above models and other models, Tang & Ali (2013) and Tang (2019a) showed that the predicted velocity distribution by the above mentioned models is acceptable only for certain experimental datasets, but they do not agree with other datasets. In addition, the predictions by these models show significant differences even for the same dataset.…”
Section: Introductionmentioning
confidence: 96%
“…The complexity of vegetated channel flow can be interpreted in multiple mechanisms over the depth of flow (Katul et al, 2011;Nikora et al, 2013;Huai et al, 2014). The multiple mechanisms over different layers of flow can be modelled independently (Carollo et al, 2002;Huai et al, 2014;Tang, 2018aTang, , 2018bSingh et al, 2019). As a pre-requisite for the analysis in resistance and pollutant mixing process of flow and so on, the vertical velocity distribution in vegetated channel flow has drawn great attention of researchers (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations